A Novel Prognostic Nomogram Based on TIGIT and NKG2A Can Predict Relapse‐Free Survival of Hepatocellular Carcinoma After Hepatectomy - Junqi Wang; Yuqing Cao; Yu Tian; Chaoliu Dai; Tianqiang Jin; Feng Xu (Cancer Medicine)
ABSTRACT Background and Objectives Hepatocellular carcinoma (HCC) is a major global health concern, and emerging evidence suggests that TIGIT and NKG2A are potential immune checkpoints with implications for HCC progression. This study aimed to evaluate the prognostic significance of TIGIT and NKG2A expression in HCC patients who underwent radical liver resection. Methods We conducted a retrospective analysis of 144 HCC patients who underwent radical liver resection. TIGIT and NKG2A expression levels were assessed using the immunoreactive score. Cox proportional hazards models were utilized to analyze the association between TIGIT/NKG2A expression and clinical characteristics, relapse‐free survival (RFS), and overall survival (OS). Prognostic models for OS and RFS was developed and validated using concordance index and calibration curves. Additionally, the random forest algorithm was employed to identify independent risk factors for OS and RFS and their correlation with predicted survival. Results TIGIT and NKG2A expression were identified as independent risk factors for RFS, while TIGIT expression alone significantly impacted OS. The prognostic models showed good discriminative ability, with concordance indices exceeding 0.7 for predicting 1‐, 3‐, and 5‐year OS or RFS. Calibration curves confirmed the reliability of the nomograms for OS and RFS prediction. The areas under the ROC curve consistently exceeded 0.7 for predicting OS and RFS. Elevated levels of TIGIT and NKG2A expression were associated with diminished RFS, highlighting their importance as prognostic factors. Conclusions Our study establishes the prognostic significance of TIGIT and NKG2A expression in predicting OS and RFS following radical liver resection for HCC patients. The developed prognostic models incorporating TIGIT and NKG2A expression hold promise for improving risk stratification and clinical management of HCC patients.